Estereolitografía en Odontología: Revisión bibliográfica - Leiva, Noemí (2017)
Stereolithography is the most common prototyping system used in dentistry, the efficient use of Stereolithography in dentistry is well documented in literature and in practice. It has multiple aplications, especially in orthodontics, implantology, maxillofacial surgery and maxillofacial traumatology. Despite the high cost of the machines used in this technique, each day this technology is more present in the daily practice of dentists, as an auxiliary resource for complex cases.